GPi DBS treatment outcome in children with monogenic dystonia: a case series and review of the literature - Chudy, Darko; Raguž, Marina; Vuletić, Vladimira; Rački, Valentino; Papić, Eliša; Nenadić Baranašić, Nataša; Barišić, Nina (Frontiers in Neurology, 2023)
Introduction Dystonia is the third most common pediatric movement disorder and is often difficult to treat. Deep brain stimulation (DBS) of the internal pallidum (GPi) has been demonstrated as a safe and effective treatment for genetic dystonia in adolescents and adults. The results of DBS in children are limited to individual cases or case series, although it has been proven to be an effective procedure in carefully selected pediatric cohorts. The aim of our study was to present the treatment outcome for 7- to 9-year-old pediatric patients with disabling monogenic isolated generalized DYT-THAP1 and DYT-KMT2B dystonia after bilateral GPi-DBS. Patients and results We present three boys aged <10 years; two siblings with disabling generalized DYT-THAP1 dystonia and a boy with monogenic-complex DYT-KMT2B. Dystonia onset occurred between the ages of 3 and 6. Significantly disabled children were mostly dependent on their parents. Pharmacotherapy was inefficient and patients underwent bilateral GPi-DBS. Clinical signs of dystonia improved significantly in the first month after the implantation and continued to maintain improved motor functions, which were found to have improved further at follow-up. These patients were ambulant without support and included in everyday activities. All patients had significantly lower Burke–Fahn–Marsden Dystonia Rating Scale (BFMDRS) values, indicating >25% improvement over the first 15 months. However, there was a decline in speech and upper limb function, manifesting with bradylalia, bradykinesia, and dysphonia, which decreased after treatment with trihexyphenidyl. Conclusion Although reports of patients with monogenic dystonia, particularly DYT-THAP1, treated with DBS are still scarce, DBS should be considered as an efficient treatment approach in children with pharmacoresistent dystonia, especially with generalized monogenic dystonia and to prevent severe and disabling symptoms that reduce the quality of life, including emotional and social aspects. Patients require an individual approach and parents should be properly informed about expectations and possible outcomes, including relapses and impairments, in addition to DBS responsiveness and related improvements. Furthermore, early genetic diagnosis and the provision of appropriate treatments, including DBS, are mandatory for preventing severe neurologic impairments.